Graphite phase carbon nitride coated supported noble metal catalyst, and preparation method and application thereof

CN117960225BActive Publication Date: 2026-10-09ZHEJIANG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410125208.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-30
Publication Date
2026-10-09
Estimated Expiration
2044-01-30

AI Technical Summary

Technical Problem

硝基苯催化加氢合成对氨基酚,是一条绿色、高效的合成工艺,但缺点是对氨基酚选择性低,并且贵金属催化剂在强酸性的反应环境中,贵金属易流失,导致催化剂失活

Benefits of technology

[0031] (1) The preparation method of the present invention uses simple and readily available raw materials and is easy to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004687964480000011
    Figure HDA0004687964480000011
  • Figure HDA0004687964480000012
    Figure HDA0004687964480000012
Patent Text Reader

Abstract

The application discloses a graphite phase carbon nitride coated supported noble metal catalyst and a preparation method and application thereof. The preparation method of the graphite phase carbon nitride coated supported noble metal catalyst comprises the following steps: (1) preparing graphite phase carbon nitride; (2) preparing a supported noble metal catalyst; (3) taking the supported noble metal catalyst, stirring and mixing at room temperature for 1-4 hours, then adding hydrogen peroxide and continuing to stir for 2-4 hours, then adding graphite phase carbon nitride solid powder, immersing at room temperature for 1-12 hours, vacuum drying until moisture is dried, ball-milling the obtained dry product, and placing the ball-milled product in a tube furnace to obtain the graphite phase carbon nitride coated noble metal catalyst through calcination. The application provides application of the graphite phase carbon nitride coated supported noble metal catalyst in preparation of p-aminophenol through nitrobenzene hydrogenation rearrangement, and the catalyst has high stability, high activity and high selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a graphite-phase carbon nitride-coated supported noble metal catalyst and its preparation method, as well as its application in the hydrogenation of nitrobenzene to p-aminophenol. Background Technology

[0002] p-Aminophenol is an important chemical raw material and organic intermediate, widely used in pharmaceuticals, dyes, antioxidants, photosensitive materials, and pesticides. The catalytic hydrogenation of nitrobenzene to synthesize p-aminophenol is a green and efficient synthesis process, but its disadvantages include low selectivity for p-aminophenol and the tendency for precious metal catalysts to leach out in strongly acidic reaction environments, leading to catalyst deactivation.

[0003] Therefore, encapsulating precious metal particles with an insoluble, acid-insoluble inert material and then inventing a supported precious metal catalyst with good catalytic hydrogenation activity and stability in a strongly acidic environment is one of the effective methods to avoid the loss of precious metals.

[0004] Graphitic carbon nitride (g-C3N4) is a relatively new polymer semiconductor material. Its components are readily available C and N elements in the natural environment. It exhibits good resistance to acid and alkali corrosion, good chemical stability, and easily tunable structure and properties. Compared to other inorganic semiconductor materials, it is easy to synthesize, contains no metal elements, is low-cost, and environmentally friendly. Furthermore, carbon nitride materials possess a porous surface structure, large specific surface area, and numerous active sites. Summary of the Invention

[0005] The purpose of this invention is to provide a graphite-phase carbon nitride-coated supported noble metal catalyst, its preparation method, and its application in the hydrogenation of nitrobenzene to p-aminophenol. The preparation method of this catalyst is simple, green, and efficient, and the prepared graphite-phase carbon nitride-coated supported noble metal catalyst exhibits high stability, high activity, and high selectivity when applied to the hydrogenation of nitrobenzene to p-aminophenol.

[0006] To achieve the above-mentioned objectives, the technical solution adopted by the present invention is as follows:

[0007] In a first aspect, the present invention provides a method for preparing a graphitic carbon nitride-coated supported noble metal catalyst, comprising the following steps:

[0008] (1) Preparation of graphitic carbon nitride: After grinding the nitrogen source compound thoroughly, it is placed in a muffle furnace for high-temperature pyrolysis. The high-temperature pyrolysis conditions are: heating to 450-600℃ at a heating rate of 1-10℃ / min, holding the reaction for 1-24h, and grinding the pyrolysis product to obtain graphitic carbon nitride solid powder; the nitrogen source compound is at least one of melamine, urea, and dicyandiamide;

[0009] (2) Preparation of supported noble metal catalyst: The carbon source was added to an aqueous solution of ethylene glycol (which also serves as a solvent and reducing agent) and stirred and mixed. The mixture was then ultrasonically dispersed at room temperature. Subsequently, an ethylene glycol solution of the noble metal source was slowly added to the solution, while an aqueous solution of sodium hydroxide or ammonia was slowly added to control the pH of the reaction system to be greater than 7.5. The mixture was thoroughly mixed under ultrasonication and placed in an oil bath and heated at 130–140 °C for 2–4 h under an inert atmosphere. The mixture was then filtered, washed, and vacuum dried to obtain the supported noble metal catalyst.

[0010] (3) Preparation of graphite phase carbon nitride-coated supported noble metal catalyst: Take the supported noble metal catalyst obtained in step (2), add water and stir at room temperature for 1-4 hours, then add hydrogen peroxide and continue stirring for 2-4 hours, then add graphite phase carbon nitride solid powder and impregnate at room temperature for 1-12 hours, vacuum dry until the moisture is dried, ball mill the obtained dried product and place it in a tube furnace for calcination to obtain graphite phase carbon nitride-coated supported noble metal catalyst. The calcination is carried out in an inert protective atmosphere or under vacuum, the calcination temperature is 400-800℃, the heating rate is 5-10℃ / min, and the calcination time is 2-10 hours.

[0011] Preferably, in step (1), the high-temperature pyrolysis is performed by heating to 450-550°C and holding at that temperature, with a heating rate of 5-10°C / min and a holding time of 2-5 hours.

[0012] Preferably, in step (2), the feeding ratio of the carbon source, the ethylene glycol aqueous solution, and the ethylene glycol solution of the noble metal source is 1g:50-100mL:1-10mL; the concentration of the ethylene glycol aqueous solution is 2wt%-5wt%, and the concentration of the ethylene glycol solution of the noble metal source is 0.01-0.05g / mL based on the mass concentration of the noble metal source. More preferably, in step (2), the feeding ratio of the carbon source, the ethylene glycol aqueous solution, and the ethylene glycol solution of the noble metal source is 1g:70-80mL:2-5mL, the concentration of the ethylene glycol aqueous solution is 2wt%-3wt%, and the concentration of the ethylene glycol solution of the noble metal source is 0.02-0.04g / mL based on the mass concentration of the noble metal source.

[0013] Preferably, the noble metal source in step (2) is a platinum source; further, the platinum source is chloroplatinic acid, sodium chloroplatinate or potassium chloroplatinate.

[0014] Preferably, in step (2), the concentration of the sodium hydroxide solution should be 0.5–1.5 mol / L; and the concentration of the ammonia solution should be 25 wt%–28 wt%.

[0015] Preferably, the carbon source in step (2) is at least one of activated carbon, graphene, and carbon black.

[0016] Preferably, the washing in step (2) is performed by washing with hydrochloric acid, anhydrous ethanol, and deionized water in sequence.

[0017] Preferably, in step (2), after adding sodium hydroxide aqueous solution or ammonia to control the pH of the reaction system to be >7.5, the mixture is sonicated for 0.5 to 2 hours.

[0018] Preferably, in step (2), the vacuum drying temperature should be 80-100℃ and the vacuum drying time should be no less than 10h.

[0019] Preferably, the hydrogen peroxide concentration in step (3) is 2-5 wt%, and the mass ratio of hydrogen peroxide, supported noble metal catalyst, and graphitic carbon nitride solid powder is 0.5-1:1:0.1-0.8. More preferably, the mass ratio of hydrogen peroxide, supported noble metal catalyst, and carbon nitride solid powder is 0.5-1:1:0.1-0.5.

[0020] As a preferred option, a planetary ball mill is used for ball milling in step (3), and the ball milling conditions are: rotation speed of 400-600 rpm and ball milling time of 2-3 h.

[0021] Preferably, in step (3), the calcination temperature is 400-600℃ and the calcination time is 2-5h.

[0022] In a second aspect, the present invention provides a graphite-phase carbon nitride-coated supported noble metal catalyst prepared according to the preparation method described in the first aspect.

[0023] This invention protects active metals under acidic reaction conditions by using graphitic carbon nitride as a carbon layer to coat the active metal. Graphitic carbon nitride is a planar two-dimensional sheet structure similar to graphene. Due to its unique chemical composition and π-conjugated electronic structure, it has strong nucleophilicity, high electronic conductivity, and high mechanical strength. Its unique porous structure can effectively buffer volume expansion and prevent the active material from detaching. Because the noble metal is covered by a carbon layer of specific structure and thickness, platinum will not be lost when it is in an acidic hydrogenation environment. Furthermore, after the noble metal is coated by the carbon layer of specific structure and thickness, electrons can penetrate the carbon layer through the quantum tunneling effect, maintaining catalytic performance while improving the selectivity of the target product.

[0024] Thirdly, the present invention provides the application of the graphite-phase carbon nitride-coated supported noble metal catalyst in the hydrogenation rearrangement of nitrobenzene to prepare p-aminophenol.

[0025] The specific method of the application is as follows: Deionized water, 98wt% concentrated sulfuric acid, nitrobenzene, surfactant, and graphite-phase carbon nitride-coated supported noble metal catalyst are added to an acid-resistant high-pressure reactor. Hydrogen gas is introduced and a hydrogenation rearrangement reaction is carried out under stirring conditions. The reaction conditions are controlled as follows: temperature is 60-130℃, hydrogen pressure is 0.6-1.2MPa, and rotation speed is 500-1000rpm to obtain the target product p-aminophenol.

[0026] Preferably, the ratio of graphitic carbon nitride-coated noble metal catalyst to nitrobenzene is 0.2-1.0 g: 8 mL, more preferably 0.4-0.6 g: 8 mL.

[0027] Preferably, the surfactant is hexadecyltrimethylammonium chloride or hexadecyltrimethylammonium bromide. Further, the feed ratio of deionized water, concentrated sulfuric acid, hexadecyltrimethylammonium chloride or hexadecyltrimethylammonium bromide and nitrobenzene is 60-80 mL: 5-7 mL: 0.08-0.10 g: 8 mL.

[0028] Preferably, the reaction temperature of the hydrogenation rearrangement reaction is 90–110°C, and the hydrogen pressure inside the reactor is 0.7–1.0 MPa.

[0029] This invention records the amount of hydrogen consumed during the hydrogenation reaction. The reaction endpoint is indicated by a significant decrease in reaction temperature or a sharp decrease in the amount of hydrogen added per unit time. After the reaction is completed, the reaction solution is obtained by filtration, diluted to volumetric flask, and an appropriate amount of the reaction solution is taken for liquid chromatography analysis. The conversion rate and selectivity of the reaction are calculated by external standard method.

[0030] Compared with the prior art, the advantages of the present invention are as follows:

[0031] (1) The preparation method of the present invention uses simple and readily available raw materials and is easy to operate.

[0032] (2) The catalyst prepared by the present invention is applied to the reaction of catalytic hydrogenation of nitrobenzene to prepare p-aminophenol without the need for additives. It has good catalytic performance, high conversion rate, high selectivity, high catalyst stability and long life. Therefore, the catalyst of the present invention has good stability in the hydrogenation reaction in sulfuric acid environment. The catalyst was used 10 times in a row without obvious deactivation. Attached Figure Description

[0033] Figure 1 , Figure 2 This is a TEM image of the graphitic carbon nitride-coated supported noble metal catalyst prepared in Example 2. The structure of the metal dots coated on the carbon layer can be seen in the image. Detailed Implementation

[0034] The present invention will be further described below through specific embodiments, but the scope of protection of the present invention is not limited thereto:

[0035] Quantitative analysis of PAP was performed using high performance liquid chromatography (C18 column 4.6*150, mobile phase: V). 乙腈 :V 水 =60 / 40, flow rate: 1.0 mL / min, column temperature: 30℃, wavelength: 254 nm). The microwave generator is an MCR-3 atmospheric pressure microwave chemical reactor.

[0036] Example 1

[0037] Take 2g of urea and grind it thoroughly in a corundum mortar. Then add it to a crucible and place it in a muffle furnace. Heat the furnace from room temperature to 520℃ at a heating rate of 5℃ / min and keep it at that temperature for 4 hours. Let it cool naturally to room temperature. Then take out the solid and grind it to obtain graphite phase carbon nitride material.

[0038] Take 1g of activated carbon (average pore size: 3.5nm, specific surface area: 1502m²). 2 The platinum-containing compound (e.g., chloroplatinic acid hexahydrate) was added to 75 mL of 2% wt ethylene glycol aqueous solution and sonicated for 1 h. 2.76 mL of chloroplatinic acid hexahydrate / ethylene glycol solution (chloroplatinic acid hexahydrate content 0.03 g / mL) was added to the sonicated solution, and 1.32 mol / L sodium hydroxide aqueous solution was slowly added simultaneously to control the pH of the reaction system to > 7.5, followed by sonication for 1 h. The mixture was placed in an oil bath, heated at 130 °C for 2 h under nitrogen atmosphere, and the product was filtered. It was then washed successively with hydrochloric acid, anhydrous ethanol, and deionized water until the pH of the filtrate reached 7. The filtrate was then vacuum dried at 80 °C for 12 h and cooled to room temperature. A supported noble metal catalyst was prepared, with a platinum loading of 3% wt.

[0039] 1 g of supported noble metal catalyst was mixed in 50 mL of deionized water and stirred for 2 h. Then, 0.5 g of 2% wt hydrogen peroxide was added during the stirring process. After stirring for 4 h, 0.3 g of graphitic carbon nitride solid was added and impregnated at room temperature for 8 h. The mixture was then placed in a vacuum drying oven to dry the moisture. The dried product was ball-milled at 400 rpm for 2 h using a planetary ball mill. Then, it was placed in a quartz boat and placed in a tube furnace. The temperature was increased from room temperature to 550 °C at a heating rate of 5 °C / min and held at that temperature for 4 h. After naturally cooling to room temperature, the catalyst was collected and packaged to obtain graphitic carbon nitride-coated supported noble metal catalyst.

[0040] In a 250 mL autoclave, 0.4 g of the prepared graphitic carbon nitride-coated supported noble metal catalyst, 8 mL of nitrobenzene, 70 mL of deionized water, 6 mL of concentrated sulfuric acid (98% wt), and 0.09 g of hexadecyltrimethylammonium chloride were added sequentially. The air was purged with nitrogen five times, followed by purging the nitrogen in the reactor three times with hydrogen. The temperature was raised to 70 °C, and hydrogen was introduced to maintain a pressure of 1.0 MPa. Stirring was initiated at a rate of 1000 rpm, and the reaction was maintained at a constant temperature until the reaction endpoint (characterized by a sharp decrease in the amount of hydrogen added per unit time by approximately two orders of magnitude) was reached. The reaction solution was then removed, filtered to remove the catalyst, and the filtrate was diluted to a 250 mL volumetric flask. Analyzing the solution using high-performance liquid chromatography (HPLC) with external standard method, the conversion rate of nitrobenzene was 99.8%, and the selectivity for p-aminophenol was 77.4%.

[0041] Example 2

[0042] Take 2g of melamine and grind it thoroughly in a corundum mortar. Then add it to a crucible and place it in a muffle furnace. Heat the furnace from room temperature to 520℃ at a heating rate of 5℃ / min and keep it at that temperature for 4 hours. Let it cool naturally to room temperature. Then take out the solid and grind it to obtain graphite phase carbon nitride material.

[0043] Take 1g of activated carbon (average pore size: 3.5nm, specific surface area: 1502m²). 2 The platinum hexahydrate (0.03 g / mL) was added to 75 mL of 2% wt ethylene glycol aqueous solution and sonicated for 1 h. 2.76 mL of chloroplatinic acid hexahydrate / ethylene glycol solution (chloroplatinic acid hexahydrate content 0.03 g / mL) was added to the sonicated solution, and 1.32 mol / L sodium hydroxide aqueous solution was slowly added simultaneously to control the pH of the reaction system to >7.5, followed by sonication for 1 h. The mixture was placed in an oil bath and heated at 130 °C for 2 h under nitrogen purging. The product was filtered and washed successively with hydrochloric acid, anhydrous ethanol, and deionized water until the pH of the filtrate reached 7. It was then vacuum dried at 80 °C for 12 h and cooled to room temperature. A supported noble metal catalyst with a platinum loading of 3% wt was obtained.

[0044] 1 g of supported noble metal catalyst was mixed in 50 mL of deionized water and stirred for 2 h. Then, 0.5 g of 2% wt hydrogen peroxide was added during the stirring process. After stirring for 2 h, 0.3 g of graphitic carbon nitride solid was added and impregnated at room temperature for 12 h. The mixture was then placed in a vacuum drying oven to dry the moisture. The dried product was ball-milled at 400 rpm for 2 h using a planetary ball mill. Then, it was placed in a quartz boat and placed in a tube furnace. The temperature was increased from room temperature to 520℃ at a heating rate of 5℃ / min and held at that temperature for 2 h. After naturally cooling to room temperature, the catalyst was collected and packaged to obtain graphitic carbon nitride-coated supported noble metal catalyst.

[0045] In a 250 mL autoclave, 0.4 g of the prepared graphitic carbon nitride-coated supported noble metal catalyst, 8 mL of nitrobenzene, 70 mL of deionized water, 6 mL of concentrated sulfuric acid (98% wt), and 0.09 g of hexadecyltrimethylammonium chloride were added sequentially. The air in the reactor was replaced with nitrogen five times, followed by hydrogen replacement three times. The temperature was raised to 100 °C, and hydrogen was introduced to maintain a pressure of 1.0 MPa. Stirring was initiated at a rate of 1000 rpm, and the reaction was maintained at a constant temperature until the endpoint was reached. The reaction solution was removed, filtered to remove the catalyst, and the filtrate was diluted to a 250 mL volumetric flask. Analyzing the solution using high-performance liquid chromatography (HPLC) with external standard method, the conversion rate of nitrobenzene was 99.9%, and the selectivity for p-aminophenol was 85.6%.

[0046] Example 3

[0047] Take 2g of melamine, grind it thoroughly in a corundum mortar, add it to a crucible and place it in a muffle furnace. Heat it from room temperature to 450℃ at a heating rate of 10℃ / min, keep it at the temperature for 2 hours, and let it cool naturally to room temperature. Then take out the solid and grind it to obtain graphitized carbon nitride material.

[0048] 1 g of carbon black was added to 75 mL of 2% wt ethylene glycol aqueous solution and sonicated for 1 h. 2.76 mL of chloroplatinic acid hexahydrate / ethylene glycol solution (chloroplatinic acid hexahydrate content 0.03 g / mL) was added to the sonicated solution, and 1.32 mol / L sodium hydroxide aqueous solution was slowly added simultaneously to control the pH of the reaction system to >7.5, followed by sonication for 1 h. The mixture was placed in an oil bath and heated at 130 °C for 2 h under nitrogen atmosphere. The product was filtered and washed successively with hydrochloric acid, anhydrous ethanol, and deionized water until the pH of the filtrate reached 7. It was then vacuum dried at 80 °C for 12 h and cooled to room temperature. A supported noble metal catalyst with a platinum loading of 3% wt was prepared.

[0049] 1 g of supported noble metal catalyst was mixed in 50 mL of deionized water and stirred for 2 h. Then, 0.5 g of 2% wt hydrogen peroxide was added during the stirring process. After stirring for 2 h, 0.4 g of graphitic carbon nitride solid was impregnated at room temperature for 12 h. The mixture was then dried in a vacuum drying oven. The dried product was ball-milled at 400 rpm for 2 h using a planetary ball mill. The product was then placed in a quartz boat and placed in a tube furnace. The temperature was increased from room temperature to 450 °C at a heating rate of 10 °C / min and held at that temperature for 2 h. The product was then naturally cooled to room temperature, collected, and packaged to obtain the graphitic carbon nitride-coated supported noble metal catalyst.

[0050] In a 250 mL autoclave, 0.4 g of the prepared graphitic carbon nitride-coated supported noble metal catalyst, 8 mL of nitrobenzene, 70 mL of deionized water, 6 mL of concentrated sulfuric acid (98% wt), and 0.09 g of hexadecyltrimethylammonium chloride were added sequentially. The air was replaced with nitrogen five times, followed by hydrogen replacement three times. The temperature was raised to 100 °C, and hydrogen was introduced to maintain a pressure of 1.0 MPa. Stirring was initiated at a rate of 1000 rpm, and the reaction was maintained at a constant temperature until the endpoint was reached. The reaction solution was removed, filtered to remove the catalyst, and the filtrate was diluted to a 250 mL volumetric flask. Analyzing by high-performance liquid chromatography (HPLC) using the external standard method, the conversion rate of nitrobenzene was 99.7%, and the selectivity for p-aminophenol was 77.6%.

[0051] Example 4

[0052] Take 2g of urea and grind it thoroughly in a corundum mortar. Then add it to a crucible and place it in a muffle furnace. Heat the furnace from room temperature to 520℃ at a heating rate of 5℃ / min and keep it at that temperature for 4 hours. Let it cool naturally to room temperature. Then take out the solid and grind it to obtain graphite phase carbon nitride material.

[0053] Take 1g of activated carbon (average pore size: 3.5nm, specific surface area: 1502m²). 2 The platinum hexahydrate (0.03 g / mL) was added to 75 mL of 2% wt ethylene glycol aqueous solution and sonicated for 1 h. 2.76 mL of chloroplatinic acid hexahydrate / ethylene glycol solution (chloroplatinic acid hexahydrate content 0.03 g / mL) was added to the sonicated solution, and 1.32 mol / L sodium hydroxide aqueous solution was slowly added simultaneously to control the pH of the reaction system to >7.5, followed by sonication for 1 h. The mixture was placed in an oil bath and heated at 130 °C for 2 h under nitrogen purging. The product was filtered and washed successively with hydrochloric acid, anhydrous ethanol, and deionized water until the pH of the filtrate reached 7. It was then vacuum dried at 80 °C for 12 h and cooled to room temperature. A supported noble metal catalyst with a platinum loading of 3% wt was obtained.

[0054] 1 g of supported noble metal catalyst was mixed in 50 mL of deionized water for 2 h. Then, 0.5 g of 2% wt hydrogen peroxide was added during the stirring process. After stirring for 4 h, 0.3 g of graphitic carbon nitride solid was impregnated at room temperature for 8 h. The mixture was then dried in a vacuum drying oven. The dried product was ball-milled at 400 rpm for 2 h using a planetary ball mill. The product was then placed in a quartz boat and placed in a tube furnace. The temperature was increased from room temperature to 550 °C at a heating rate of 5 °C / min and held at that temperature for 4 h. The product was then naturally cooled to room temperature, collected, and packaged to obtain the graphitic carbon nitride-coated supported noble metal catalyst.

[0055] In a 250 mL autoclave, 0.5 g of the prepared graphitic carbon nitride-coated supported noble metal catalyst, 8 mL of nitrobenzene, 60 mL of deionized water, 7 mL of concentrated sulfuric acid (98% wt), and 0.09 g of hexadecyltrimethylammonium bromide were added sequentially. The air in the reactor was replaced with nitrogen five times, followed by hydrogen replacement three times. The temperature was raised to 70 °C, and hydrogen was introduced to maintain a pressure of 1.0 MPa. Stirring was initiated at a rate of 1000 rpm, and the reaction was maintained at a constant temperature until the endpoint was reached. The reaction solution was removed, filtered to remove the catalyst, and the filtrate was diluted to a 250 mL volumetric flask. Analyzing the solution using high-performance liquid chromatography (HPLC) with external standard method, the conversion rate of nitrobenzene was 99.2%, and the selectivity for p-aminophenol was 72.2%.

[0056] Example 5

[0057] Example 5 investigated the application performance of the graphite-phase carbon nitride-coated supported metal catalyst prepared in Example 2 in the hydrogenation rearrangement of nitrobenzene to prepare p-aminophenol in Example 2.

[0058] Table 1. Stability of graphite-phase carbon nitride-coated supported metal catalysts in the hydrogenation rearrangement of nitrobenzene to prepare p-aminophenol.

[0059] 1 99.9% 84.3% 2 99.1% 85.1% 3 99.3% 82.9% 4 99.2% 84.8% 5 99.0% 83.3% 6 99.5% 83.5% 7 99.3% 84.1% 8 99.3% 84.9% 9 99.1% 82.9% 10 99.1% 84.2%

[0060] Comparative Example 1

[0061] Take 1g of activated carbon (average pore size: 3.5nm, specific surface area: 1502m²). 2 The platinum hexahydrate (0.03 g / mL) was added to 75 mL of 2% wt ethylene glycol aqueous solution and sonicated for 1 h. 2.76 mL of chloroplatinic acid hexahydrate / ethylene glycol solution (chloroplatinic acid hexahydrate content 0.03 g / mL) was added to the sonicated solution, and 1.32 mol / L sodium hydroxide aqueous solution was slowly added simultaneously to control the pH of the reaction system > 7.5, followed by sonication for 1 h. The mixture was placed in an oil bath and heated at 130 °C for 2 h under nitrogen atmosphere. The product was filtered and washed successively with hydrochloric acid, anhydrous ethanol, and deionized water until the pH of the filtrate was 7. It was then vacuum dried at 80 °C for 12 h and cooled to room temperature. A supported noble metal catalyst was prepared with a platinum loading of 3% wt. No carbon nitride coating was applied to the supported noble metal catalyst.

[0062] In a 250 mL autoclave, 0.4 g of the prepared graphitic carbon nitride-coated supported noble metal catalyst, 8 mL of nitrobenzene, 70 mL of deionized water, 6 mL of concentrated sulfuric acid (98% wt), and 0.09 g of hexadecyltrimethylammonium chloride were added sequentially. The air in the reactor was replaced with nitrogen five times, followed by hydrogen replacement three times. The temperature was raised to 100 °C, and hydrogen was introduced to maintain a pressure of 1.0 MPa. Stirring was initiated at a rate of 1000 rpm, and the reaction was maintained at a constant temperature until the endpoint was reached. The reaction solution was removed, filtered to remove the catalyst, and the filtrate was diluted to a 250 mL volumetric flask. Analyzing the solution using high-performance liquid chromatography (HPLC) with external standard method, the conversion rate of nitrobenzene was 99.1%, and the selectivity for p-aminophenol was 55.6%.

[0063] Comparative Example 2

[0064] Take 2g of melamine and grind it thoroughly in a corundum mortar. Then add it to a crucible and place it in a muffle furnace. Heat the furnace from room temperature to 520℃ at a heating rate of 5℃ / min and keep it at that temperature for 4 hours. Let it cool naturally to room temperature. Then take out the solid and grind it to obtain graphite phase carbon nitride material.

[0065] 1 g of commercial 3 wt% Pt / C catalyst (Degong Chemical Co., Ltd.) was mixed with 50 mL of deionized water for 2 h. Then, 0.5 g of 2 wt% hydrogen peroxide was added during the stirring process. After stirring for 2 h, 0.3 g of graphitic carbon nitride solid was added and impregnated at room temperature for 12 h. The mixture was then placed in a vacuum drying oven to dry the moisture. The dried product was ball-milled at 400 rpm for 2 h using a planetary ball mill. Then, it was placed in a quartz boat and placed in a tube furnace. The temperature was increased from room temperature to 520℃ at a heating rate of 5℃ / min and held at that temperature for 2 h. After naturally cooling to room temperature, the product was collected and packaged to obtain a graphitic carbon nitride-coated supported noble metal catalyst.

[0066] In a 250 mL autoclave, 0.4 g of the prepared graphitic carbon nitride-coated supported noble metal catalyst, 8 mL of nitrobenzene, 70 mL of deionized water, 6 mL of concentrated sulfuric acid (98% wt), and 0.09 g of hexadecyltrimethylammonium chloride were added sequentially. The air in the reactor was replaced with nitrogen five times, followed by hydrogen replacement three times. The temperature was raised to 100 °C, and hydrogen was introduced to maintain a pressure of 1.0 MPa. Stirring was initiated at a rate of 1000 rpm, and the reaction was maintained at a constant temperature until the endpoint was reached. The reaction solution was removed, filtered to remove the catalyst, and the filtrate was diluted to a 250 mL volumetric flask. Analyzing by high-performance liquid chromatography (HPLC) using the external standard method, the conversion rate of nitrobenzene was 99.3%, and the selectivity for p-aminophenol was 68.9%.

Claims

1. A method for preparing a graphite-phase carbon nitride-coated supported noble metal catalyst for the hydrogenation rearrangement of nitrobenzene to p-aminophenol, characterized in that: The preparation method includes the following steps: (1) Preparation of graphitic carbon nitride: After grinding the nitrogen source compound thoroughly, it is placed in a muffle furnace for high-temperature pyrolysis. The high-temperature pyrolysis conditions are: heating to 450-600 °C at a heating rate of 1-10 °C / min, holding the reaction at this temperature for 1-24 h, and grinding the pyrolysis product to obtain graphitic carbon nitride solid powder; the nitrogen source compound is at least one of melamine, urea, and dicyandiamide; (2) Preparation of supported noble metal catalyst: The carbon source was added to an ethylene glycol aqueous solution and stirred and mixed. The mixture was ultrasonically dispersed at room temperature. Then, the ethylene glycol solution of the noble metal source was slowly added to the solution. At the same time, sodium hydroxide aqueous solution or ammonia was slowly added to control the pH value of the reaction system to be >7.

5. The mixture was thoroughly mixed under ultrasonication and placed in an oil bath and heated at 130-140℃ for 2-4 hours under an inert atmosphere. Then, the mixture was filtered, washed, and vacuum dried to obtain the supported noble metal catalyst. (3) Preparation of graphite phase carbon nitride coated supported noble metal catalyst: Take the supported noble metal catalyst obtained in step (2), add water and stir at room temperature for 1-4 hours, then add hydrogen peroxide and continue stirring for 2-4 hours, then add graphite phase carbon nitride solid powder and impregnate at room temperature for 1-12 hours, vacuum dry until the moisture is dried, ball mill the obtained dried product and place it in a tube furnace for calcination to obtain graphite phase carbon nitride coated supported noble metal catalyst. The calcination is carried out in an inert protective atmosphere or vacuum, the calcination temperature is 400-800℃, the heating rate is 5-10℃ / min, and the calcination time is 2-10 hours.

2. The preparation method according to claim 1, characterized in that: In step (1), the high-temperature pyrolysis is as follows: heating to 450-550 ℃ and holding at that temperature, with a heating rate of 5-10 ℃ / min and a holding time of 2-5 h.

3. The preparation method according to claim 1, characterized in that: In step (2), the feeding ratio of carbon source, ethylene glycol aqueous solution and precious metal source ethylene glycol solution is 1g:50-100 mL:1-10 mL; the concentration of the ethylene glycol aqueous solution is 2wt%-5wt%, and the concentration of the precious metal source ethylene glycol solution is 0.01-0.05g / mL based on the mass concentration of the precious metal source.

4. The preparation method according to claim 1, characterized in that: In step (2), the feeding ratio of carbon source, ethylene glycol aqueous solution and precious metal source ethylene glycol solution is 1g:70-80mL:2-5mL, the concentration of the ethylene glycol aqueous solution is 2wt%-3wt%, and the concentration of the precious metal source ethylene glycol solution is 0.02-0.04g / mL based on the mass concentration of the precious metal source.

5. The preparation method according to claim 1, characterized in that: The precious metal source mentioned in step (2) is a platinum source; the platinum source is chloroplatinic acid, sodium chloroplatinate or potassium chloroplatinate; the carbon source is at least one of activated carbon, graphene and carbon black.

6. The preparation method according to claim 1, characterized in that: The hydrogen peroxide concentration in step (3) is 2-5 wt%, and the mass ratio of hydrogen peroxide, supported noble metal catalyst and graphite phase carbon nitride solid powder is 0.5-1:1:0.1-0.

8.

7. The preparation method according to claim 1, characterized in that: In step (3), the calcination temperature is 400-600℃ and the calcination time is 2-5h.

8. A graphite-phase carbon nitride-coated supported noble metal catalyst for the preparation of p-aminophenol by hydrogenation rearrangement of nitrobenzene, prepared by any one of claims 1-7.

9. The application of the graphite-phase carbon nitride-coated supported noble metal catalyst as described in claim 8 in the hydrogenation rearrangement of nitrobenzene to prepare p-aminophenol.

10. The application as described in claim 9, characterized in that: The specific method of the application is as follows: Deionized water, 98wt% concentrated sulfuric acid, nitrobenzene, surfactant, and graphite-phase carbon nitride-coated supported noble metal catalyst are added to an acid-resistant high-pressure reactor. Hydrogen gas is introduced and a hydrogenation rearrangement reaction is carried out under stirring conditions. The reaction conditions are controlled as follows: temperature of 60-130℃, hydrogen pressure of 0.6-1.2 MPa, and rotation speed of 500-1000 rpm to obtain the target product p-aminophenol.

Citation Information

Patent Citations

  • Preparation method and application of carbon-doped coated platinum catalyst

    CN114308024A